PROTOTYPE SWITCH OTOMATIS PADA KAMERA GAMMA DENGAN PENGENDALI JARAK JAUH BERBASIS ARDUINO - Rezki Setiawan; Rachmat Ramdani (JURNAL TEKNOLOGI INDUSTRI, 2020)
The use and use of radioactive and in the industrial sector, is increasing in Indonesia. Radiography and one of them, is used to examine the structure and quality of materials, using the Non-Destructive Test method. Currently, gamma cameras are still used, manually, namely the operator who operates the camera directly, and causes health problems by gamma ray radiation.      One solution is to design a control system on a gamma camera, for that, several components are needed to produce the desired work system. The components used for the system are Arduino Uno, radio frequency and servo motors.    As for activating, it begins by pressing a switch to open or close the gamma camera in order to minimize health hazards from gamma ray radiation, Prototype is made with a ratio of 1: 2.Red LEDs, green LEDs, and LCDs are used as indicators for operators that the device is well connected System measurement testing, carried out with radio frequency with and without hindrance to variations in distance of 5 m, 10m, 15m, 20m and 25m, the system can still work, and is well connected. Keywords: gamma camera, arduino uno, radio frequency.